PEMANFAATAN LIMBAH KULIT PISANG MENJADI PUPUK CAIR ORGANIK PENYUBUR TANAMAN DI DESA ROCEK KECAMATAN CIMANUK KABUPATEN PANDEGLANG - Gabriel Jonathan C. S. G; Raihan Rabby Zahran; Shofi Rochmania Heryanti; Lewis Binsar Hangoluan; Widya Rahmadinni; Nurul Imanah Imanah M; Annisa Khotimah; Sierfi Rahayu (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Utilization and management of the potential owned by the village, need to be done to increase the results that are economical and beneficial for the lives of the village community. The potential of Rocek Village is in the agricultural sector. Banana peel waste, something that initially has no value and even ends up as waste. This community service activity is needed to increase knowledge if banana peel waste is processed and reprocessed, it can produce something more useful such as organic liquid fertilizer. general steps in making liquid organic fertilizer from banana peels: preparation of ingredients, fermentation, fermentation digestion, and use. How to apply organic liquid fertilizer from banana peels is after the fermentation process is complete, the liquid fertilizer can be applied to plants. The method is by spraying it on the plants. When spraying, make sure the fertilizer does not touch the stems and leaves of the plant, especially on plants that are exposed to direct sunlight. Keywords: Banana Peel, Organic Fertilizer, Rocek Village